Benchmarking selected machine tool manufacturing firms in China - Yang, Hong; Tabucanon, Mario T.; Paul, Himangshu; Bohez, Erik L.J.; Government of the Netherlands (Bangkok : Asian Institute of Technology, 1994)
This study proposes a quantitative approach for benchmarking machine tools manufacturing firms. It focuses on the efficiency of the firms in the Beijing area. Comparisons were done among rnachine tools manufacturing firms in Beijing, Shanghai, selected European countries, U.S. and Japan. Gaps were found and analyzed. Data Envelopment Analysis (DEA) model was applied to identify the efficient and inefficient Decision Making Units (DMU) which were represented by Beijing machine tools manufacturing firms in this study. This process was done by two levels: the firm level and the production system level. The sensitivity analysis also was done in two levels. The recommendations were given to raise the DMUs' efficiency score. Through the analysis, we find that firms in Beijing should adopt more new technology in their production management and improve the performance in sales forecast comparing with global manufacturing practices. They also, should emphasis on the overseas sales and reduce the number of employees at the firm level, and improve the quality of products and the level of computer use in production planning and scheduling at production system level.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Production management -- China